Porous ammonia synthesis catalyst, its preparation method and use

The porous ammonia synthesis catalyst addresses the inefficiencies of conventional catalysts by enabling low-temperature, low-pressure ammonia synthesis with improved stability and reduced energy consumption, offering a cost-effective and environmentally friendly solution.

JP2025503822AActive Publication Date: 2025-02-06ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023560222
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-02-06
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

Conventional ammonia synthesis catalysts require high temperature and high pressure conditions, leading to high energy consumption, environmental contamination, and catalyst instability, necessitating the development of a catalyst that can operate efficiently under low temperature and low pressure with improved stability and reduced energy consumption.

Method used

A porous ammonia synthesis catalyst produced via a sol-gel method using a metal complex as a template agent and silicon source, incorporating metal ions and organic ligands, with a silicate backbone and adjustable pore size and metal composition, allowing for efficient ammonia synthesis at lower reaction conditions.

Benefits of technology

The catalyst achieves high efficiency, low energy consumption, and environmental friendliness with adjustable pore size and metal distribution, enhancing stability and reducing production costs, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503822000001_ABST
    Figure 2025503822000001_ABST
Patent Text Reader

Abstract

The present invention discloses a porous ammonia synthesis catalyst suitable for catalyzing an ammonia synthesis reaction using nitrogen gas and hydrogen gas as raw materials, its preparation method, and use. The porous ammonia synthesis catalyst is a novel ammonia synthesis catalyst material prepared by using a metal coordination compound as a template, uniformly dispersing the metal coordination compound in silica gel by a sol-gel method, then performing hydrothermal aging, and finally controlling the calcination conditions. Compared with conventional synthetic ammonia catalysts, the porous ammonia synthesis catalyst of the present invention has a uniform pore distribution, easy to adjust the pore size, large specific surface area, and easy to adjust the degree of aggregation of metal active centers, particle size, distribution, structure, and composition. The ammonia synthesis catalyst is highly efficient, can catalyze ammonia synthesis under mild reaction conditions, has high stability, and has low catalyst production costs, and can completely replace conventional industrial catalysts for ammonia synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of ammonia synthesis catalyst production, in particular to a porous ammonia synthesis catalyst, its production method and use. [Background technology]

[0002] Ammonia is one of the most important raw materials for the synthesis of chemical products and fertilizers, and in recent years, it has been expected to be applied in the field of hydrogen storage. Haber first used an iron-based catalyst to prepare ammonia from hydrogen and nitrogen under high temperature and pressure conditions in 1904, and Bosch realized the industrialization of ammonia in 1913. Since then, research on ammonia synthesis has attracted attention and developed rapidly. Almquist et al. investigated the relationship between the activity of pure iron catalysts and iron components of different valences and found that Fe3O4-based catalysts were the most active. Bridger et al. discovered that the introduction of both Al2O3-K2O additives extremely increased the catalytic activity of iron-based catalysts. In 1979, the Imperial Chemical Industry of the UK first used cobalt oxide as an additive to develop the Fe2Co catalyst, further improving the catalytic activity. In 1985, Liu Huazhang et al. 1-x It was discovered that O-based catalysts have higher catalytic activity for ammonia synthesis, and this led to their commercialization. In 1992, BP and Kellogg Company of the United States jointly developed the O-based catalyst and its process flow (KAAP), which was recognized as the second generation ammonia synthesis catalyst.

[0003] Iron-based catalysts used in industrial ammonia synthesis are prepared by melting Fe3O4 and different types of promoters (Al2O3, CaO, K2O, etc.) at a temperature of about 2000K. Moreover, the ammonia synthesis process needs to be carried out under high temperature (400-600℃) and high pressure (10-30MPa) conditions, which has the disadvantages of high energy consumption (1%-2% of the world's annual energy consumption) and large amounts of greenhouse gases (CO2, etc.) being emitted. The harsh reaction conditions can also lead to serious sintering of the catalyst and loss of active sites. Ruthenium-based catalysts have poor stability (easily sintered and agglomerated under high temperature conditions, prone to hydrogen poisoning), and are more expensive to manufacture than inexpensive transition metals. Therefore, the development of new catalysts that are inexpensive, environmentally friendly, have low energy consumption, are more stable, and can realize ammonia synthesis under mild conditions has become an important research topic in the current era. Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide a porous ammonia synthesis catalyst, a manufacturing method and its use, which can efficiently catalyze ammonia synthesis under low temperature and pressure conditions, and which is expected to be used as an alternative to conventional industrial ammonia synthesis catalysts, in order to address the problems existing in conventional ammonia synthesis catalysts. [Means for solving the problem]

[0005] The porous ammonia synthesis catalyst is produced by a sol-gel method using a metal complex as a template agent and a silicon source as a raw material, the metal complex being a compound formed by a metal ion and an organic ligand via a coordinate bond, the metal ion being one or more of boron, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, iron, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, dysprosium, cesium, sodium, potassium, magnesium, calcium, and barium ions mixed in a compounding ratio, and the organic ligand being an organic compound in which two or more elements of nitrogen, phosphorus, and oxygen atoms are mixed in a compounding ratio.

[0006] Furthermore, the organic ligand is preferably a carboxylic acid ligand, and said carboxylic acid ligand is preferably one or more of benzoic acid, pyridine carboxylic acid, terephthalic acid, formic acid, acetic acid, propionic acid, 1-naphthoic acid, 2-naphthoic acid.

[0007] Furthermore, the silicon source is preferably a silicate ester, sodium metasilicate, and the silicate ester is preferably one or more of methyl orthosilicate, tetraethyl orthosilicate, tetrabutyl orthosilicate, tetraisopropyl orthosilicate.

[0008] Furthermore, the porous ammonia synthesis catalyst is a silicate catalyst material containing metal active centers, in which the molar ratio of silicon to metal active centers is 2-100:1.

[0009] Furthermore, the porous ammonia synthesis catalyst has a specific surface area of ​​50 to 800 m 2 / g, and the pore size is 1 to 10 nm.

[0010] Furthermore, the porous ammonia synthesis catalyst is an iron-based catalyst, and the metal ions are a mixture of iron ions and other promoter element ions in a compounding ratio, and the other promoter element ions are one or more of boron, sodium, potassium, magnesium, calcium, barium, cesium, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, and dysprosium ions.By introducing iron active centers in situ into the porous metal silicate material and doping it with various promoter elements, the catalytic efficiency of the catalyst is greatly improved.

[0011] The method for producing the porous ammonia synthesis catalyst includes the steps of producing the porous ammonia synthesis catalyst by a sol-gel method, adding a silicon source to a metal carboxylate solution, stirring until the solution is sufficiently dissolved, and then placing the solution in a hydrothermal reaction vessel, placing the hydrothermal reaction vessel in an oven to carry out a hydrothermal reaction to form a gel, drying the gel, transferring the gel to a muffle furnace, carrying out a programmable heating process in an air atmosphere up to 100 to 1000°C, and calcining at a constant temperature for 1 to 24 hours, or placing the gel in a tubular furnace, heating to 100 to 1000°C in an inert atmosphere, and calcining at a constant temperature for 1 to 24 hours, thereby obtaining a porous ammonia synthesis catalyst.

[0012] Furthermore, the metal carboxylate solution is prepared by dissolving a carboxylate ligand and a metal salt in a solvent at a molar ratio of 0.5 to 10:1, and the metal ions in the metal salt are one or more of boron, sodium, potassium, magnesium, calcium, barium, cesium, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, iron, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, and dysprosium ions mixed in an arbitrary ratio, and the solvent is one or more of water, methanol, ethanol, N,N-dimethylformamide, acetonitrile, and acetone mixed in an arbitrary ratio.

[0013] Furthermore, the metal carboxylate is preferably a benzoate, and the metal salt is dissolved in a solvent at a molar ratio of 1-5:0.5-1.

[0014] Furthermore, the concentration of metal ions in the metal carboxylate solution is 0.1 to 1 mmol / L.

[0015] Furthermore, metal salts are substances that dissolve in solvents, such as chlorides, nitrates, acetates, and sulfates.

[0016] Furthermore, the hydrothermal reaction conditions are 80°C to 200°C and 6 hours to 48 hours.

[0017] Use of the porous ammonia synthesis catalyst in an ammonia synthesis reaction.

[0018] The specific operation is as follows: the porous ammonia synthesis catalyst is mixed with quartz sand and filled into a reactor, the reaction gas is a nitrogen-hydrogen mixed gas with a nitrogen-hydrogen ratio of 0.1 to 10:1, and the reaction conditions are 0.1 to 15 MPa, reaction temperature 150 to 450°C, and reaction space velocity 1 to 72 L g -1 h -1 Let us assume that. Effect of the Invention

[0019] Compared with the prior art, the present invention has the following advantages: 1. The porous ammonia synthesis catalyst of the present invention has low preparation cost, simple process, and no pollution. 2. The pore size of the porous ammonia synthesis catalyst can be adjusted by adjusting the compounding ratio of silicon and metal ions, the composition of metal ions, etc., and it has a large specific surface area and uniform pore distribution. 3. The active metal components and structure, particle size and distribution of the porous ammonia synthesis catalyst can be easily adjusted by adjusting the compounding ratio of silicon and metal ions, and the aggregation degree of the metal active center can be easily adjusted, thereby improving the catalytic efficiency. 4. When the porous ammonia synthesis catalyst is used in catalytic ammonia synthesis reaction, the reaction temperature and pressure can be lowered, the energy consumption can be lowered, the catalytic efficiency can be higher, the stability can be higher and it is environmentally friendly. This can solve the problems of high energy consumption and pollution existing in traditional industrial catalysts, and the industrial application of the porous ammonia synthesis catalyst is expected to become more widespread. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a graph showing the performance of ammonia synthesis catalytic activity of PMS-100, PMS-100-a, and DNCA type ammonia synthesis catalysts under various temperature conditions at a pressure of 2 MPa. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention discloses a porous ammonia synthesis catalyst, its preparation method and its use, which has a porous metal silicate as a framework and one or more metals as catalytic active centers in a predetermined ratio, and has low raw material costs, is easy to prepare, and consumes little energy.When this porous ammonia synthesis catalyst is used as a catalyst for ammonia synthesis, the reaction pressure and temperature are low, the catalytic efficiency is high, there is no pollution, and it can be used for a long time with high activity. The following examples are provided to aid in understanding the present invention, but are not intended to limit the scope of the invention. Example 1

[0022] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), cesium chloride (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 °C for 3 hours. After cooling to room temperature, the mixture was left stirring overnight. The mixture was placed in a hydrothermal reactor and aged at 160 °C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 600 °C for 5 hours to obtain a solid material, which was named PMS-100. This porous ammonia synthesis catalyst has a specific surface area of ​​427 m2 / g, the pore distribution was uniform, and the average pore diameter was 0.96 nm. Example 2

[0023] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 °C for 3 hours. After cooling to room temperature, the mixture was left stirring overnight. The mixture was placed in a hydrothermal reactor and aged at 160 °C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 600 °C for 5 hours to obtain a solid material, which was named PMS-100-a. This porous ammonia synthesis catalyst has a specific surface area of ​​475 m 2 / g, the pore distribution was uniform, and the average pore diameter was 0.83 nm. Example 3

[0024] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), calcium chloride (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 °C for 3 hours. After cooling to room temperature, the mixture was left stirring overnight. The mixture was placed in a hydrothermal reactor and aged at 160 °C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 °C in an air atmosphere to obtain a solid material, which was named PMS-100-b. This porous ammonia synthesis catalyst has a specific surface area of ​​456 m 2 / g, the pore distribution was uniform, and the average pore diameter was 0.90 nm. Example 4

[0025] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), boric acid (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 ° C for 3 hours. The mixture was then cooled to room temperature and stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 160 ° C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 ° C in an air atmosphere to obtain a solid material, which was named PMS-100-c. This porous ammonia synthesis catalyst had a uniform pore distribution and was similar in specific surface area and average pore size to the materials in the above examples. Example 5

[0026] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), aluminum chloride (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 ° C for 3 hours. After cooling to room temperature, the mixture was left overnight with stirring. The mixture was placed in a hydrothermal reactor and aged at 160 ° C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 ° C in an air atmosphere to obtain a solid material, which was named PMS-100-d. The porous ammonia synthesis catalyst had a uniform pore distribution, and the specific surface area and average pore size were similar to those of the materials in the above examples. Example 6

[0027] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), aluminum chloride (0.112 mmol), potassium nitrate (0.224 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 ° C for 3 hours. After cooling to room temperature, the mixture was left overnight with stirring. The mixture was placed in a hydrothermal reactor and aged at 160 ° C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 ° C in an air atmosphere to obtain a solid material, which was named PMS-100-e. The porous ammonia synthesis catalyst had a uniform pore distribution, and the specific surface area and average pore size were similar to those of the materials in the above examples. Example 7

[0028] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), chromium nitrate (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and the mixture was stirred at 120 ° C for 3 hours, cooled to room temperature, and then stirred overnight. The mixture was placed in a hydrothermal reaction vessel and aged at 160 ° C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 ° C in an air atmosphere to obtain a solid material, which was named PMS-100-f. This porous ammonia synthesis catalyst had a uniform pore distribution, and the specific surface area and average pore size were similar to those of the materials in the above examples. Example 8

[0029] Benzoic acid (13.44 mmol), iron nitrate (2.24 mmol), cerium chloride (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and the mixture was stirred at 120 ° C for 3 hours, cooled to room temperature, and then stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 160 ° C for 24 hours to gel. The dried solid was transferred to a muffle furnace and calcined at 600 ° C in an air atmosphere to obtain a solid material, which was named PMS-100-g. The porous ammonia synthesis catalyst had a uniform pore distribution, and the specific surface area and average pore size were similar to those of the materials in the above examples. Example 9

[0030] The activity of the catalyst was evaluated in a high-pressure activity test device with an inner diameter of 8 mm. The catalysts produced in Examples 1 to 8 or commercially available catalysts (see Table 1 for specific amounts used) were mixed with a specified amount of quartz sand and filled into a stainless steel reactor. The reaction gas was a nitrogen-hydrogen mixed gas with a nitrogen-hydrogen ratio of 1:3, the reaction pressure was 2 MPa, the reaction temperature was 350°C, and the reaction space velocity was 9 L g -1 h -1 The reaction gas was absorbed with a dilute sulfuric acid aqueous solution, and the ammonium ion concentration in the absorbent was measured by ion chromatography. From the results shown in Table 1, when the catalyst of the present invention was used as a catalyst for ammonia synthesis, the catalytic efficiency was much higher than that of the DNCA-type industrial ammonia synthesis catalyst and the commercial ruthenium carbon catalyst, which shows that the present invention has a promising future for industrial application. (Table 1) Comparison table of synthetic ammonia performance test results for Examples 1 to 10, Comparative Example 1 and Comparative Example 2 TIFF2025503822000002.tif130161 Example 10

[0031] 0.2 g of PMS-100 / PMS-100-a / DNCA were mixed with a specified amount of quartz sand and charged into a stainless steel reactor. The reaction gas was a nitrogen-hydrogen mixed gas with a nitrogen-hydrogen ratio of 1:3, the reaction pressure was 2 MPa, the reaction temperature was increased from 250 to 400 °C at a rate of 25 °C, and the reaction space velocity was 9 L g-1 h -1 The reaction gas was absorbed with a dilute sulfuric acid aqueous solution at each temperature, and the ammonium ion concentration in the absorbent was measured by ion chromatography. From the results shown in Figure 1, the efficiency of the catalyst of the present invention is much higher than that of the DNCA-type industrial ammonia synthesis catalyst. Example 11

[0032] Benzoic acid (26.88 mmol), iron nitrate (4.48 mmol), cobalt nitrate (0.112 mmol), and tetraethyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 ° C for 3 hours. After cooling to room temperature, the mixture was left stirring overnight. The mixture was placed in a hydrothermal reaction vessel and aged at 100 ° C for 12 hours to gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 400 ° C for 8 hours to obtain a solid material. This porous ammonia synthesis catalyst has a uniform pore distribution, a specific surface area and an average pore size similar to those of the materials in the above examples, and has good ammonia synthesis catalytic efficiency. Example 12

[0033] Formic acid (13.44 mmol), platinum nitrate (1.344 mmol), and methyl orthosilicate (6.72 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120°C for 3 hours. The mixture was then cooled to room temperature and stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 120°C for 16 hours to form a gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 100°C for 24 hours to obtain a solid material. This porous ammonia synthesis catalyst has a uniform pore distribution, a specific surface area and an average pore size similar to those of the materials in the above examples, and good ammonia synthesis catalytic efficiency. Example 13

[0034] Acetic acid (1.12 mmol), cobalt nitrate (2.24 mmol), and sodium metasilicate (6.72 mmol) were added to 4 mL of water and stirred at 100°C for 4 hours, cooled to room temperature, and then stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 200°C for 20 hours to gel. The dried solid was transferred to a tube furnace and calcined at 600°C for 1 hour in a nitrogen gas atmosphere to obtain a solid material. This porous ammonia synthesis catalyst has a uniform pore distribution, a specific surface area and an average pore size similar to those of the materials in the above examples, and good ammonia synthesis catalytic efficiency. Example 14

[0035] Terephthalic acid (13.44 mmol), rhodium chloride (2.24 mmol), cesium chloride (0.112 mmol), and chlorosilane (235.2 mmol) were added to a mixed solvent of 4 mL of N,N-dimethylformamide and 0.5 mL of water, and stirred at 120 ° C for 3 hours. The mixture was then cooled to room temperature and stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 160 ° C for 36 hours to form a gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 600 ° C for 4.5 hours to obtain a solid material. This porous ammonia synthesis catalyst has a uniform pore distribution, a specific surface area and an average pore size similar to those of the materials in the above examples, and good ammonia synthesis catalytic efficiency. Example 15

[0036] 1-Naphthoic acid (13.44mmol), iron nitrate (2.24mmol), cerium chloride (0.112mmol), and tetraisopropyl orthosilicate (6.72mmol) were added to a mixed solvent of 4mL of N,N-dimethylformamide and 0.5mL of water, and stirred at 120°C for 3 hours. The mixture was then cooled to room temperature and stirred overnight. The mixture was placed in a hydrothermal reactor and aged at 200°C for 48 hours to form a gel. The dried solid was transferred to a muffle furnace and calcined in an air atmosphere at 600°C for 5 hours to obtain a solid material. This porous ammonia synthesis catalyst has a uniform pore distribution, a specific surface area and an average pore size similar to those of the materials in the above examples, and has good ammonia synthesis catalytic efficiency.

[0037] The above are only some of the embodiments of the present invention, and any equivalent changes and modifications made based on the patent scope of the present application are within the scope of the present invention.

Claims

1. A porous ammonia synthesis catalyst produced by a sol-gel method using a metal complex as a template and a silicon source as a raw material, The metal complex is a compound formed by a coordinate bond between a metal ion and an organic ligand, The metal ions are one or more of boron, sodium, potassium, magnesium, calcium, barium, cesium, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, iron, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, and dysprosium ions, mixed in any mixing ratio; The organic ligand is an organic compound containing one or more of nitrogen, phosphorus, and oxygen atoms; A porous ammonia synthesis catalyst.

2. 2. The porous ammonia synthesis catalyst according to claim 1, wherein the organic ligand is a carboxylic acid ligand.

3. The porous ammonia synthesis catalyst according to claim 2, characterized in that the carboxylic acid ligand is one or more of benzoic acid, pyridine carboxylic acid, terephthalic acid, formic acid, acetic acid, propionic acid, 1-naphthoic acid, and 2-naphthoic acid.

4. The porous ammonia synthesis catalyst according to claim 1, characterized in that the silicon source is a silicate ester, sodium metasilicate, or chlorosilane, and the silicate ester is one or more of methyl orthosilicate, tetraethyl orthosilicate, tetrabutyl orthosilicate, and tetraisopropyl orthosilicate.

5. The porous ammonia synthesis catalyst according to claim 1, characterized in that the porous ammonia synthesis catalyst is a silicate catalyst material containing metal active centers, in which the molar ratio of silicon to metal active centers is 2:1 to 100:

1.

6. Specific surface area is 50 to 800 m 2 2. The porous ammonia synthesis catalyst according to claim 1, characterized in that the pore size is 1 to 10 nm.

7. The porous ammonia synthesis catalyst according to any one of claims 1 to 6, characterized in that the metal ions are a mixture of iron ions and other promoter element ions in a compounding ratio, and the other promoter element ions are one or more of boron, sodium, potassium, magnesium, calcium, barium, cesium, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, and dysprosium ions.

8. The method for producing the porous ammonia synthesis catalyst according to claim 1, characterized in that a silicon source is added to a metal carboxylate solution, and after sufficient dissolution, the solution is placed in a hydrothermal reaction kettle, and the hydrothermal reaction kettle is placed in an oven to carry out a hydrothermal reaction to form a gel, and the gel is dried and transferred to a muffle furnace, and a programmed temperature rise is performed in an air atmosphere to 100 to 1000°C, and the temperature is maintained and calcined for 1 to 24 hours, or the gel is dried and placed in a tubular furnace, and the temperature is raised to 100 to 1000°C in an inert atmosphere, and the temperature is maintained and calcined for 1 to 24 hours, thereby obtaining a porous ammonia synthesis catalyst.

9. The metal carboxylate solution is prepared by dissolving a carboxylic acid ligand and a metal salt in a solvent in a molar ratio of 0.5 to 10:1, the metal ions in the metal salt are one or more of boron, sodium, potassium, magnesium, calcium, barium, cesium, aluminum, zirconium, nickel, titanium, cobalt, manganese, vanadium, chromium, iron, copper, zinc, tungsten, platinum, ruthenium, rhodium, palladium, lanthanum, cerium, praseodymium, samarium, neodymium, and dysprosium ions mixed in a mixing ratio, and the solvent is one or more of water, methanol, ethanol, N,N-dimethylformamide, acetonitrile, and acetone mixed in an arbitrary mixing ratio. The method for producing a porous ammonia synthesis catalyst according to claim 8.

10. Use of the porous ammonia synthesis catalyst according to any one of claims 1 to 6 in an ammonia synthesis reaction.

Citation Information

Patent Citations

  • Preparation method of dual-activity monatomic ammonia synthesis catalyst

    CN108435179A

  • Composite catalyst for synthesizing ammonia and preparation method and application thereof

    CN109999858A

  • Preparation and application of porous metal silicate material and of porous metal silicate material

    CN113275016A

  • Catalyst for synthesizing ammonia

    JP2007029858A

  • Heterogeneous catalysts / process based on supported / grafted transition metal hydrides for ammonia formation from nitrogen and hydrogen

    US20190185333A1